Reconstructing Zakat Governance in Indonesia: A Maqāṣid al-Sharī‘ah Approach to Constitutional Reform - A Hashfi Luthfi; Ali Sodiqin; Moh. Tamtowi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2026)
Recent reforms in Indonesia’s zakat governance have intensified debates concerning the balance between state authority and civil society participation, particularly following Constitutional Court Decisions No. 97/PUU-XXII/2024 and No. 54/PUU-XXIII/2025. Existing studies on zakat governance have predominantly emphasized managerial efficiency, institutional performance, and administrative accountability, while paying limited attention to the constitutional implications of zakat regulation and its alignment with the normative objectives of Islamic law. This study addresses this gap by examining how zakat governance in Indonesia can be reconstructed through the integration of constitutional principles, good governance, and maqāṣid al-sharī‘ah. The study aims to examine the extent to which the current zakat management framework aligns with the objectives of maqāṣid al-sharī‘ah, evaluate the institutionalization of good governance principles, and formulate a participatory governance model that balances state authority with civil society involvement. Employing a normative legal research design, this study utilizes statutory, conceptual, and maqāṣidī approaches through doctrinal analysis of Law No. 23 of 2011 on Zakat Management and relevant Constitutional Court decisions. The findings reveal that Indonesia’s zakat governance remains structurally centralized under BAZNAS, generating institutional imbalances and weakening participatory accountability. Although the Constitutional Court upheld the legality of the current framework, it simultaneously mandated reforms to strengthen transparency, accountability, and public participation. This study proposes a maqāṣid-based good zakat governance model grounded in dual oversight and institutional checks and balances to promote distributive justice, public welfare, and sustainable zakat governance.